Asymptotic stability of integral sets - Ignat'ev, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove theorems on asymptotic, equiasymptotic, and uniform asymptotic stability of the integral sel of a nonautonomous system of ordinary differential equations.